Monitoring perceived stress, recovery and submaximal performance during preparation and competition in elite female athletes - Otter, R. T. A.; Brink, M. S.; Lemmink, K. A. P. M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Elite athletes enhance their performance by physical training. However, it is suggested that performance is also affected by perceived stress and recovery (Kentta and Hassmen, 1998). The purpose of this study was to analyze the relationship between changes in perceived stress, recovery and submaximal performance during the preparation and competition phase. Methods: Fourteen competitive female athletes (9 ice skaters, 3 tri-athletes and 2 cyclists; age, 27 ± 9 years; height, 171 ± 5 cm; weight, 62 ± 5 kg and VO2max, 50 ± 5 mL/min/kg), completed 4 questionnaires (Dutch RESTQ-sport) in which perceived stress and recovery were measured (Nederhof et al., 2008) followed by 4 HR-based submaximal cycling tests (LSCT, Lamberts et al., 2011) before the preparation phase (T1), during the preparation phase (T2), at the beginning of the competition phase (T3) and during the competition phase (T4). The LSCT protocol involves athletes to perform 6 minutes at 60% of maximal heart rate (HRmax) followed by 6 minutes at 80%HRmax and 3 minutes at 90%HRmax. Performance was measured as the mean power output over the last 2 minutes at 90%HRmax (PO90). Results: PO90 (i.e. performance) changed by -3 ± 19 W (T2-T1), -2 ± 14 W (T3-T2) and 3 ± 17 W (T4-T3), respectively. Changes in general stress, general recovery, sportspecific stress and sport-specific recovery ranged from -0.8 ± 3 to 0.1 ± 2.0 for T2-T1 (i.e. preparation phase), -1.3 ± 1.7 to 1.3 ± 2.2 for T3-T2 (i.e. preparation to competition phase) and -0.3 ± 1.3 to 0.9 ± 2.4 for T4-T3 (i.e. within the competition phase). No relationships were found between PO90 and perceived stress and recovery within the period of the preparation to the start of the competition phase (T1, T2 and T3). However, increased sport-specific recovery was related to increased PO90 during the competition phase (T4-T3) (r=0.59, p=0.04). Discussion: It is shown that a higher perceived sport-specific recovery is related to better submaximal performance during the competition phase of elite female athletes. This implicates that the lack of recovery may result in decreased performance. Monitoring perceived recovery during the competition phase can provide insights that can help to optimise training programs of female athletes by means of appropriate recovery strategies/interventions.